(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained the extent authentic assessment strategies are utilized for academicimprovement in business education programme in colleges of education in South-East Nigeria. Tworesearch questions guided the study and two null hypotheses were tested. Descriptive survey researchdesign was adopted for the study. The population comprised 158 business educators in the sevenpublic colleges of education in South-East, Nigeria. The entire population was studied without sampling because the size was not too large. The instrument for data collection was a 22-itemstructured questionnaire. The instrument was validated by three experts. Cronbach’s alpha was usedto determine the internal consistency of the items, which yielded apha values of 0.91 and 0.90. Meanand standard deviation were used to answer the research questions, while t-test was used to test thenull hypotheses at 0.05 alpha levels. The findings of the study revealed that colleges of educationbusiness educators lowly utilized portfolios and moderately utilized projects assessment strategies for academic improvement in South-East Nigeria. Colleges of education. It was found that business educators’ years of teaching experience significantly influence the extent of utilization of portfolios and projects assessment strategies for academic improvement. It was recommended among others that business education lecturers in colleges of education should endeavor to provide regular feedbacktotheir students as regards their achievements in various authentic assessment procedures.